Melacak Jejak Sejarah Bentuk Tari Serai Serumpun Sebagai Identitas Budaya Kabupaten Mesuji Provinsi Lampung - I Wayan Mustika; Tuntun Sinaga; Iing Sunarti (Mudra Jurnal Seni Budaya, 2022)
This research is a dance ethnographic study that was conducted to trace the history of the serai serumpun dance which has lost its history. In the past, this dance was thought to have originally belonged to the Mesuji community and was an asset of the Mesuji Regency Education Office as well as the identity of the Mesuji Community of Lampung Province. This research will first discuss the form of the serai serumpun dance which is studied through the discipline of ethnochoreology. Then an assessment will also be made of the supporting culture of the serai serumpun dance, so as to obtain the values contained in it. By knowing these values, an identity of the people of Mesuji Regency will be obtained through the history of the serai serumpun dance.